How Heavy Is an Illusory Length? - Anouk J. de Brouwer; Jeroen B. J. Smeets; Myrthe A. Plaisier (i-Perception, 2016)
The perception of object properties, such as size and weight, can be subject to illusions. Could a visual size illusion influence perceived weight? Here, we tested whether the size-weight illusion occurs when lifting two physically identical but perceptually different objects, by using an illusion of size. Participants judged the weight and length of 11 to 17 cm brass bars with equal density to which cardboard arrowheads were attached to create a Müller–Lyer illusion. We found that these stimuli induced an illusion in which the bar that was visually perceived as being shorter was also perceived as feeling heavier. In fact, a 5-mm increase in illusory length corresponded to a decrease in illusory weight of 15 g.